A case with massive hemobilia long-term after internal drainage surgery for congenital biliary dilation - Shunryo Minezaki; Takeyuki Misawa; Makoto Watanabe; Hideki Takahashi; Takashi Koenuma; Rie Kondo; Hiroe Toyoda; Kentaro Nemoto; Hiroyuki Tsukayama; Makoto Shibuya; Keita Wada; Keiji Sano; et al. (Surgical Case Reports)
Abstract Background Currently, there is an unwavering consensus that the standard surgery for congenital biliary dilation (CBD) is extrahepatic bile duct resection and choledochojejunostomy. However, decades prior, choledochocyst–gastrointestinal anastomosis without extrahepatic bile duct resection (internal drainage surgery, IDS) was preferred for CBD because of its simplicity. Currently, there is almost no chance of a surgeon encountering a patient who has undergone old-fashioned IDS, which has been completely obsolete due to the risk of carcinogenesis from the remaining bile duct. Moreover, the pathological condition long after IDS is unclear. Herein, we report a case of life-threatening bile duct bleeding as well as carcinoma of the bile duct 62 years after IDS in a patient with CBD. Case presentation An 82-year-old Japanese woman with hemorrhagic shock due to gastrointestinal bleeding was transferred to our hospital. She had a medical history of unspecified surgery for CBD at the age of 20. Based on imaging findings and an understanding of the historical transition of the surgical procedure for CBD, the cause of gastrointestinal bleeding was determined to be rupture of the pseudoaneurysm of the dilated bile duct that remained after IDS. Hemostasis was successfully performed by transcatheter arterial embolization (TAE) in an emergency setting. Then, elective surgery for extrahepatic bile duct resection and choledochojejunostomy was performed to prevent rebleeding. Pathological examination revealed severely and chronically inflamed mucosa of the bile duct. Additionally, cholangiocarcinoma (Tis, N0, M0, pStage 0) was incidentally revealed. Conclusion It has been indicated that not only carcinogenesis, but also a risk of life-threatening bleeding exists due to long-lasting chronic inflammation to the remnant bile duct after IDS for CBD. Additionally, both knowledge of which CBD operation was performed, and an accurate clinical history are important for the diagnosis of hemobilia.